Capping protein and the Arp2/3 complex regulate nonbundle actin filament assembly to indirectly control actin bundle positioning during Drosophila melanogaster bristle development. - Frank, D.J.; Hopmann, R.; Lenartowska, M.; Miller, K.G. (Molecular Biology of the Cell, 2006)
Drosophila melanogaster bristle development is dependent on actin assembly, and prominent actin bundles form against the elongating cell membrane, giving the adult bristle its characteristic grooved pattern. Previous work has demonstrated that several actin-regulating proteins are required to generate normal actin bundles. Here we have addressed how two actin regulators, capping protein, a barbed end binding protein, and the Arp2/3 complex, a potent actin assembly nucleator, function to generate properly organized bundles. As predicted from studies in motile cells, we find that capping protein and the Arp2/3 complex act antagonistically to one another during bristle development. However, these proteins do not primarily act directly on bundles, but rather on a dynamic population of actin filaments that are not part of the bundles. These nonbundle filaments, termed snarls, play an important role in determining the number and spacing of the actin bundles. Reduction of capping protein leads to an increase in snarls, which prevents actin bundles from properly attaching to the membrane. Conversely, loss of an Arp2/3 complex component leads to a loss of snarls and accumulation of excess membrane-attached bundles. These results indicate that in nonmotile cells dynamic actin filaments can function to regulate the positioning of stable actin structures. In addition, our results suggest that the Arpc1 subunit may have an additional function, independent of the rest of the Arp2/3 complex.